The legitimisation of clicktivism. Issue 1 (2nd January 2018) - Halupka, Max
ABSTRACT: Is clicking 'Like' on Facebook a legitimate form of political participation? Is changing your profile picture or sharing an online article politically meaningful? It is undeniable that such actions can be politically-themed, but whether they amount to what we term 'political participation' remains contentious. This article explores the legitimacy of clicktivism as a political act, arguing that legitimacy be understood as multifaceted. To this end, the paper develops a series of lenses by which to explore the theoretical boundaries of these emerging actions. These are: the adherence of the action to tradition avenues; the acceptance of the action, and belief in that action; and, the intentionality of the action, and the context in which it is situated.